Surgical outcomes of primary lung cancers following esophagectomy for primary esophageal carcinoma. (13th January 2021) - Komatsu, Hiroaki; Izumi, Nobuhiro; Tsukioka, Takuma; Inoue, Hidetoshi; Miyamoto, Hikaru; Ito, Ryuichi; Kimura, Takuya; Nishiyama, Noritoshi
Abstract: Background: The aim of this retrospective study is to evaluate the perioperative complications and prognosis of patients with a history of resected esophageal carcinoma who subsequently underwent pulmonary resection of a primary lung cancer. Methods: The study cohort comprised 23 patients who had undergone curative resection of a primary lung cancer following esophagectomy for a primary esophageal carcinoma. Clinical characteristics and surgical outcomes were analyzed. Results: The initial treatment for esophageal carcinoma was esophagectomy by thoracotomy in 10 patients and video assisted thoracoscopic surgery in 13. The treatments for lung cancer comprised wedge resection in three patients, segmentectomy in seven and lobectomy in 13. The pulmonary resections were performed by thoracotomy in six and video assisted thoracoscopic surgery in 17. The average operating time for the lung cancer surgeries was 202 min and average blood loss 122 ml. There were no perioperative deaths or severe complications. Three- and Five-year overall survival rates were 78.0% and 68.2%. According to univariate survival analysis, age, restrictive ventilatory impairment and histology of lung cancer were significant predictors of poor prognosis (all P  < 0.05). Significantly more of the patients with than without restrictive ventilatory impairment died of other diseases ( P  = 0.0036). Conclusions: Pulmonary resection for primary lung cancers following esophagectomy for esophageal carcinoma is acceptable in selected patients. Such surgery requires caution concerning intrathoracic adhesions and postoperative prolonged air leakage. Patients with restrictive ventilatory impairment had a poorer prognosis, and the indication for surgery in these patients should be carefully considered. Abstract : Pulmonary resection for a primary lung cancer following esophagectomy for a primary esophageal carcinoma is acceptable in selected patients. Patients with restrictive ventilatory impairment have poorer prognoses.